2013
DOI: 10.2113/jeeg18.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Imaging of Subsurface Earthquake-induced Liquefaction Features at Christchurch Boys High School, Christchurch, New Zealand

Abstract: On February 22, 2011, a magnitude M w 6.2 earthquake affected the Canterbury region, New Zealand, resulting in many fatalities. Liquefaction occurred across many areas, visible on the surface as ''sand volcanoes'', blisters and subsidence, causing significant damage to buildings, land and infrastructure.Liquefaction occurred at a number of sites across the Christchurch Boys High School sports grounds; one area in particular contained a piston ground failure and an adjacent silt volcano. Here, as part of a clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Some of the abandoned river channels can be traced through the wider area of Christchurch city and were probably active within the last 500 years (Basher et al ., ). These channel deposits were particularly prone to liquefaction, as was shown in some of the main studies undertaken to understand the correlation between liquefaction features and geomorphic setting of the CES (Almond et al ., ; Wotherspoon et al ., ; Nobes et al ., ; Bastin et al ., ; Villamor et al ., ).…”
Section: The Geomorphology and The Soils Of The Canterbury Plainsmentioning
confidence: 98%
“…Some of the abandoned river channels can be traced through the wider area of Christchurch city and were probably active within the last 500 years (Basher et al ., ). These channel deposits were particularly prone to liquefaction, as was shown in some of the main studies undertaken to understand the correlation between liquefaction features and geomorphic setting of the CES (Almond et al ., ; Wotherspoon et al ., ; Nobes et al ., ; Bastin et al ., ; Villamor et al ., ).…”
Section: The Geomorphology and The Soils Of The Canterbury Plainsmentioning
confidence: 98%
“…Results showed clear reflectors similar to what one might achieve with seismic reflection surveys ( Figure 12 [122]). Nobes et al [128], in a post-earthquake liquefaction study, combined GPR imaging with electrical imaging and demonstrated good agreement between the two methods. A key advantage to GPR surveys is the speed with which surveys can be accomplished relative to seismic surveys.…”
Section: Geophysical Techniquesmentioning
confidence: 99%
“…While a final solution about the seismogenic origin of the injection dikes must be accepted, based on geological and structural indicative criteria, preliminarily these structures and other liquefaction features might be find on GPR images. Most of GPR works conclude that sand blows on radargrams are shown as stratigraphic disruptions of the radar events and disturbance of the GPR facie [Liu, Li, 2001;Al-Shukri et al, 2006;Nobes et al, 2013;Baradello, Accaino, 2016]. Charac-teristic anomalies, the shape of which is like a funnel or a pipe with disordered and stronger reflection are additional indicators of liquefaction on GPR images [Hsu et al, 2005;Lunina, Gladkov, 2016].…”
Section: Indicative Criteria Of Injection Dikes and Other Liquefactiomentioning
confidence: 99%